Disseminated Saprochaetecapitata fungal infection in a patient with acute myeloid leukemia. Issue 4 (26th February 2021) - Duarte, Delfim; Morais, Cátia Iracema; Azevedo, Rosa; Coelho, Fernando; Martins, Anabela; Pereira, Brigitte; Coelho, Sara; Domingues, Nelson; Lebre, Ana; Trigo, Filipe; Romero, Iracema; Guimarães, Maria Augusta; et al.
Abstract: The case highlights the importance of actively obtaining informative samples at an early stage and of prompt initiation of combination therapy with antifungal drugs. Abstract : The case highlights the importance of actively obtaining informative samples at an early stage and of prompt initiation of combination therapy with antifungal drugs.